A Comparative Study of Teacher’s knowledge, Attitudes and Behavior’s Regarding Evidence Based Practices of Public and Private Universities in Lahore - Ms. Tahseen Arshad; Dr.Ghazala Noureen; Ms. Kiran Karamat (Journal of Arts & Social Sciences, 2020)
This study “A comparative study of teacher’s knowledge, attitudes and behaviors regarding Evidence-based practices of public and private universities in Lahore” investigates the difference between knowledge, attitudes and behaviors of public and private university teachers by adopting questionnaire as a tool of data collection. The study targeted the three hundred teachers of public and private universities of Lahore. The main objective of the study was to compare the knowledge, attitudes and behaviors of public and private university teachers.            Data was analyzed using descriptive and inferential statistics. The results show that overall teachers have knowledge, positive attitudes and behaviors towards Evidence-based practices. Findings of comparison indicate public sector teachers have higher knowledge and more positive attitude towards EBP as compare to private sector teachers. But on the other hand, behavior of private sector teachers was more positive than public sector teachers.Key words: Comparative, evidence-based practices, attitudes, behaviors